Production and thermal comfort of Nellore beef cattle finished in integrated crop-livestock systems - Aranha, H. S. [UNESP]; Andrighetto, C. [UNESP]; Lupatini, G. C. [UNESP]; Bueno, L. G. F. [UNESP]; Trivelin, G. A. [UNESP]; Mateus, G. P.; Luz, P. A. C. [UNESP]; Santos, J. M. F. [UNESP]; Sekiya, B. M. S. [UNESP]; Vaz, R. F. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
The objective of this work was to evaluate pasture, performace, thermal comfort, and haematological parameters of Nellore cattle in the finishing phase in integrated crop-livestock systems with two tree densities (ICLF-1L=196 ha(-1) trees and ICLF-3L=448 ha(-1) trees) and in full sun (ICL). The forage mass morphological composition of the pasture average daily gain, weight gain per area, stocking rate of the animals were evaluated in summer and autumn, and the climatic variables of systems we evaluated at three different times, and haematological parameters of the animals (n=60). The forage mass was higher in the ICL treatment and summer (P<0.05). However, the reduction of the forage mass in the ILPFs systems did not interfere with the performance of the animals (P>0.05). Ambient temperature, globe temperature and temperature and humidity index were better in shade treatments and in the morning, providing greater comfort to the animals, and was also confirmed by the lower globular volume of the bovines in ICL (P<0.05). It is concluded that the systems with trees reduce the forage mass but this reduction does not alter the animals' performance in the finishing phase. In addition, ICLFs improve the thermal comfort of the animals, however, this improvement was not enough to favor their performance.
Keywords: welfare; performance; forage mass; integrated crop-livestock-forest systems